2015
DOI: 10.1371/journal.ppat.1005034
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Drives Changes in Metabolic and Virulence Profiles of Streptococcus pneumoniae

Abstract: The bacterial pathogen, Streptococcus pneumoniae (the pneumococcus), is a leading cause of life-threatening illness and death worldwide. Available conjugate vaccines target only a small subset (up to 13) of >90 known capsular serotypes of S. pneumoniae and, since their introduction, increases in non-vaccine serotypes have been recorded in several countries: a phenomenon termed Vaccine Induced Serotype Replacement (VISR). Here, using a combination of mathematical modelling and whole genome analysis, we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
97
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(106 citation statements)
references
References 44 publications
8
97
0
Order By: Relevance
“…These results bear some similarity to previous multistrain models where linkage disequilibrium between loci emerges from the epidemiological properties of strains (21,22). In these models, unlike Number of isolates and serotypes for which carriage duration could be calculated: Massachusetts, 180 and 19; Malawi, 300 (Materials and Methods) and 9; and Maela, 2,923 and 51.…”
Section: Discussionsupporting
confidence: 83%
“…These results bear some similarity to previous multistrain models where linkage disequilibrium between loci emerges from the epidemiological properties of strains (21,22). In these models, unlike Number of isolates and serotypes for which carriage duration could be calculated: Massachusetts, 180 and 19; Malawi, 300 (Materials and Methods) and 9; and Maela, 2,923 and 51.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, a reduction of isolates belonging to ST320 19A has also been detected in a pediatric population from the USA [35] after the PCV13 introduction, even though this reduction was lower than that observed for the susceptible clones. In fact, it seems that the persistence of the ST320 19A over the remaining 19A clones may be due to a combination of factors including an improved colonizing ability [36], a change in their metabolic profile [37] and an enhanced resistance to the antimicrobial stress due its MDR pattern.…”
Section: Discussionmentioning
confidence: 99%
“…All have been demonstrated to be highly protective against 7, 10 or 13 common pneumococcal serotypes associated with carriage and disease (also termed vaccine serotypes, VT). A frequently observed consequence of PCV introduction is the increase in both carriage and disease of non-VT pneumococci (NVT), likely due to increased niche availability and reduction of competition between VT and NVT [4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…However, recently published data on nasopharyngeal carriage as measured in a cross-sectional observational study in Blantyre (Southern Malawi), four to seven years after PCV13 introduction (2015)(2016)(2017)(2018), has shown that vaccine impact (VT carriage reduction) has been slower than expected and heterogeneous across age-groups 22 . Epidemiological mathematical models have previously been employed successfully to improve our understanding of pneumococcal dynamics 5,9,[23][24][25][26][27] , as well as having contributed to explain, estimate and project PCV impact 8,11,28 . The main advantage of models is their cost-free potential to test hypotheses and gain a mechanistic, ecological and immunological understanding of carriage and disease dynamics, estimating epidemiological parameters which are difficult to otherwise quantify from raw epidemiological data.…”
Section: Introductionmentioning
confidence: 99%